2006
DOI: 10.1021/bi051669r
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability of Apolipoprotein A-I in Solution and in Discoidal High-Density Lipoprotein Probed by Double Charge Ablation and Deletion Mutation

Abstract: To identify residues and segments in the central region of apolipoprotein A-I (apoA-I) that are important for the protein structure and stability, we studied the effects of four double charge ablations, D102A/D103A, E110A/E111A, R116V/K118A, and R160V/H162A, and two deletion mutations, Δ(61-78) and Δ(121-142), on the conformation and stability of apoA-I in the lipid-free state and in reconstituted discoidal phospholipid:cholesterol:apoA-I particles (rHDL). The findings suggest that D102/D103 and E110/E111 loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 53 publications
(166 reference statements)
3
63
0
Order By: Relevance
“…The two-domain structure of apoE has been verified by the fulllength apoE3 NMR structure (32). Based on our previous mutation analysis (23)(24)(25)33) and considering that residues 185 and 186 are both glycine, we proposed a slightly different two domain structure: N-terminal domain (1-184) and C-terminal domain (185-243) (34). This analysis led to the successful crystallization and crystallographic determination of the molecular structure of the N-terminal domain (185-243) at 2.2 Å resolution (34).…”
Section: Methodsmentioning
confidence: 94%
“…The two-domain structure of apoE has been verified by the fulllength apoE3 NMR structure (32). Based on our previous mutation analysis (23)(24)(25)33) and considering that residues 185 and 186 are both glycine, we proposed a slightly different two domain structure: N-terminal domain (1-184) and C-terminal domain (185-243) (34). This analysis led to the successful crystallization and crystallographic determination of the molecular structure of the N-terminal domain (185-243) at 2.2 Å resolution (34).…”
Section: Methodsmentioning
confidence: 94%
“…Ramella et al ( 25 ) also found a destabilizing effect of the K107del mutation when apoA-I unfolding was monitored by a fl uorescent probe that refl ected changes in the tertiary conformation. Increased exposure of the hydrophobic surfaces of apoA-I[K107del] in solution (as indicated by ANS binding studies) and low cooperativity of unfolding ( Table 2 ) are consistent with a partially folded or molten globular-like conformation ( 32,39 ), which provides fl exibility and adaptability for substantial conformational changes that accompany protein binding to the surface of large lipoprotein particles. Low conformational stability facilitates the conformational changes, and greater exposure of hydrophobic surfaces of apoA-I[K107del] makes its binding to the lipid surface of TG-rich lipoproteins favorable.…”
Section: Ans Fl Uorescencementioning
confidence: 71%
“…Far-UV spectra of apoA-I in 10 mM sodium phosphate buffer (pH 7.4) were recorded at 25°C on AVIV 62DS or AVIV 215 spectropolarimeters (AVIV Associates, Inc.) at the protein concentration 25-60 g/ml, as previously described ( 31,32 ). Spectra were recorded at several protein concentrations, normalized, and expressed as mean residue ellipticity, [ ⌰ ].…”
Section: Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Amphipathic ␣ -helices have been classifi ed into several distinct classes according to the distribution of charged residues around the axis of the helix ( 12 ). The class A helix is a major lipid-binding motif of exchangeable apolipoproteins and by guest, on May 12, 2018 www.jlr.org Downloaded from nonpolar faces of the amphipathic ␣ -helices in the interior of the bundle and favorable cross-helix ion pairs ( 31 ). The helices are folded into an antiparallel bundle as depicted in Fig.…”
Section: Primary and Secondary Structuresmentioning
confidence: 99%